2005
DOI: 10.1021/bi050938a
|View full text |Cite
|
Sign up to set email alerts
|

The Seventh Transmembrane Domains of the δ and κ Opioid Receptors Have Different Accessibility Patterns and Interhelical Interactions

Abstract: We applied the substituted cysteine accessibility method (SCAM) to map the residues of the transmembrane helices (TMs) 7 of δ and κ opioid receptors (δOR and κOR) that are on wateraccessible surface of the binding-site crevices. Twenty five consecutive residues (except C7.38) in the TMs7 were mutated to Cys, one at a time, and each mutant was expressed in HEK 293 cells. Most mutants displayed similar binding affinity for [ 3 H]diprenorphine, an antagonist, as the wildtypes. Pretreatment with (2-aminoethyl) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
2
24
1
Order By: Relevance
“…We have previously demonstrated that the 45-kDa band represents N-linked glycosylated high-mannose intermediates, which mainly distribute in ER and/or cis-Golgi, whereas the 55-kDa band represents the fully glycosylated mature forms of FLAG-hKORs, most of which locate in plasma membranes (Chen et al, 2006). In addition, our receptor binding results showed that cell surface receptors accounted for ϳ85% of the total receptor (Xu et al, 2005). Cell surface receptors are the ones responding to agonists, leading to signal transduction.…”
Section: Different Regulatory Effects Of Kor Ligands On the Steady-stmentioning
confidence: 50%
“…We have previously demonstrated that the 45-kDa band represents N-linked glycosylated high-mannose intermediates, which mainly distribute in ER and/or cis-Golgi, whereas the 55-kDa band represents the fully glycosylated mature forms of FLAG-hKORs, most of which locate in plasma membranes (Chen et al, 2006). In addition, our receptor binding results showed that cell surface receptors accounted for ϳ85% of the total receptor (Xu et al, 2005). Cell surface receptors are the ones responding to agonists, leading to signal transduction.…”
Section: Different Regulatory Effects Of Kor Ligands On the Steady-stmentioning
confidence: 50%
“…We have shown previously by ligand binding that ∼80% of the receptor is located on cell surface (Xu et al, 2005), thus most of the 55-kDa band is likely located on cell surface. To evaluate whether ligands differentially regulated the FLAG-hKOR, we focused on the 55-kDa band using immunoblotting assay.…”
Section: Resultsmentioning
confidence: 81%
“…Apparently the interactions depend on the local environments. The extracellular ends of TM 1 and TM 7 are also shown in proximity in opioid receptors (Xu et al, 2005 306(7.36) in TM 7, and is able to make a H-bond network. However, no constitutive activation was observed in both receptor mutants R38A and R38K.…”
Section: Discussionmentioning
confidence: 99%